Can Graphics Tell Lies? A Tutorial on How To Visualize Your Data. Issue 4 (26th April 2018) - Cabanski, Christopher; Gilbert, Houston; Mosesova, Sofia
Abstract: Visualizations are a powerful tool for telling a story about a data set or analysis. If done correctly, visualizations not only display data but also help the audience digest key information. However, if done haphazardly, visualization has the potential to confuse the audience and, in the most extreme circumstances, deceive. In this tutorial, we provide a set of general principles for creating informative visualizations that tell a complete and accurate story of the data.